“DIALOGIC” OF ART: A HUMAN CREATIVE ASPECT - Даренський, В. Ю. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The author considers the problem of “dialogic” of art as an  essential trend in contemporary human development. The concept of ”artistic dialogue” is considered as a key this problem.